Association of vitamin D status with lower limb muscle strength in professional basketball players: A cross-sectional study - Kim, D. K.; Park, G.; Kuo, L.-T.; Park, W.-H. (Nutrients, 2020)
Vitamin D deficiency in athletes may play a role in influencing fracture risk and athletic performance. This study aimed to examine the vitamin D status of basketball players and determine its correlation with muscle strength. We included 36 male professional basketball players (mean age, 22.6 ± 3.2 years) categorized by vitamin D status. We examined the muscle strength of knee extension/flexion and ankle dorsiflexion/plantarflexion using an isokinetic dynamometer. Eleven (30.5%), fifteen (41.7%), and ten (27.8%) players had deficient (<20 ng/mL), insufficient (20-32 ng/mL), and sufficient vitamin D levels (>32 ng/mL), respectively. In the dominant side, there were no significant correlations of vitamin D level with knee extension/flexion strength (r = 0.134, p = 0.436; r = -0.017, p = 0.922, respectively), or with plantarflexion/dorsiflexion ankle strength (r = -0.143, p = 0.404; r = 1.109, p = 0.527, respectively). Moreover, the isokinetic lower limb strengths were not significantly different between the three groups in all settings (all p > 0.05). In conclusion, professional basketball players had a high prevalence of vitamin D insufficiency. Though it may not be associated with muscle strength, maintaining adequate vitamin D levels by micronutrients monitoring, regular dietician consultation, and supplementation is still a critically considerable strategy to enhance young athletes` health.